Vitamin-D-Binding Protein Contributes to the Maintenance of α Cell Function and Glucagon Secretion - Katrina Viloria; Daniela Nasteska; Linford J.B. Briant; Silke Heising; Dean P. Larner; Nicholas H.F. Fine; Fiona B. Ashford; Gabriela da Silva Xavier; Maria Jiménez Ramos; Annie Hasib; Federica Cuozzo; Jocelyn E. Manning Fox; et al. (Cell Reports, 2020)
Summary: Vitamin-D-binding protein (DBP) or group-specific component of serum (GC-globulin) carries vitamin D metabolites from the circulation to target tissues. DBP is highly localized to the liver and pancreatic α cells. Although DBP serum levels, gene polymorphisms, and autoantigens have all been associated with diabetes risk, the underlying mechanisms remain unknown. Here, we show that DBP regulates α cell morphology, α cell function, and glucagon secretion. Deletion of DBP leads to smaller and hyperplastic α cells, altered Na+ channel conductance, impaired α cell activation by low glucose, and reduced rates of glucagon secretion both in vivo and in vitro. Mechanistically, this involves reversible changes in islet microfilament abundance and density, as well as changes in glucagon granule distribution. Defects are also seen in β cell and δ cell function. Immunostaining of human pancreata reveals generalized loss of DBP expression as a feature of late-onset and long-standing, but not early-onset, type 1 diabetes. Thus, DBP regulates α cell phenotype, with implications for diabetes pathogenesis.